Development Of a Popular Scientific Book on the Population Structure of Cempedak (Artocarpus integer (Thunb.) Merr) Along the Barito Riverbank in Sungai Gampa Village, Barito Kuala Regency - Norhafizah Norhafizah; Dharmono Dharmono (Universitas Khairun, 2026)
Plant population structure refers to the existence of a group of plants within a particular area. The Cempedak plant (Artocarpus integer (Thunb.) Merr) is found growing along the Barito Riverbank in Sungai Gampa Village, Barito Kuala Regency, and has the potential to be developed as a local potential based learning resource in the form of a popular scientific book. This study aims to describe the population structure of cempedak, describe the development process, and describe the validity and readability of popular scientific books on the population structure of Cempedak as supplementary material for the plant ecology course. The method used was a total exploration method along the banks of the Barito River in Sungai Gampa Village, Barito Kuala Regency, with a length of 3.038 km and a width of 50 meters from the river's edge, along with the Plomp development model to create the popular scientific book. The results showed that (1) the population structure of Cempedak along the Barito Riverbank in Sungai Gampa Village, Barito Kuala Regency, consisted of 151.31 individuals/km² in the pre-reproductive phase, 203.94 individuals/km² in the reproductive phase, and 46.05 individuals/km² in the post-reproductive phase, with a pot- or disrupted vase shaped population pyramid, (2) the developed popular scientific book on the population structure of Cempedak followed the three phases of the Plomp development model: preliminary research, prototyping phase, and assessment phase, and (3) the instructional material in the form of a popular scientific book received a validity score of 3.35, categorized as highly valid, and a student readability score of 89%, categorized as excellent.